Border town authorities and the multilevel politics of the 'transit migrant' emergency. Issue 3 (4th May 2022) - Trucco, Daniela
ABSTRACT: The article takes the approach of multilevel politics to analyse the way the presence of illegalized 'transit migrants' is dealt with within the urban space of Ventimiglia – a medium-sized city located south of the French–Italian border – by the town government and its mayor after heightened French border controls. It focuses on the period between 2015 and 2019. Within the unneutral and criminalizing framing of 'transit migration', border towns have narrow room for political manoeuvre, and yet they can be seen as the contentious scene of migration policies and politics. Presented and justified as a pragmatic compromise between the migrants' humanitarian needs and the inhabitants' claims for security and decorum, Ventimiglia's municipal policy of encampment was built on cooperation, conflict and contestation with both higher tier authorities and grassroots civil society, thus showing an intricate system of multilevel politics. Followed by widespread discontent which partially translated into electoral disavowal, the town government's actions eventually reinforced the framing of 'transit migration' policies as emergency measures and strengthened the migrants' invisibility and precariousness in the urban space. This ethnography-based case study thus provides greater understanding of the particularities of local and multilevel migration politics in border towns and how these contribute to shape and enhance the exclusionary border regime.